The Effects of Pathogen-Associated Molecular Patterns on Peripheral Blood Monocytes in Patients with Non-alcoholic Fatty Liver Disease - Li, Qian; Rempel, Julia D.; Yang, Jiaqi; Minuk, Gerald Y. (Journal of clinical and experimental hepatology, 2022)
Innate immune responses to gut-derived pathogen-associated molecular patterns (PAMPs) have been implicated in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). Whether NAFLD patients have increased sensitivity to PAMP exposure has yet to be reported. Peripheral blood mononuclear cell (PBMC)/monocytes were exposed to lipopolysaccharide (LPS), Pam3CSK4, or BSA conjugated palmitate in vitro. Changes in toll-like receptors (TLR), cytokines, and chemokine receptors (CR) expressions were documented by flow cytometry and/or enzyme-linked immunoabsorbent assays (ELISAs). TLR2 and TLR4 expression were similar at baseline and increased to a similar extent (TLR2) or remained unchanged (TLR4) following PAMP exposure in NAFLD and healthy control (HC) monocytes. Proinflammatory IL-1β and IL-6 levels were similar at baseline but increased in a concentration-dependent manner to a greater extent in NAFLD PBMCs. CCR1 and CCR2 expressions at baseline were similar and decreased to a similar extent in NAFLD and HC monocytes. The extent of PAMP-induced proinflammatory cytokine release correlated with evidence of hepatocyte injury (CK18M30 levels). NAFLD patients have increased proinflammatory cytokine responses following exposure to PAMPs relative to HC subjects. This response is concentration-dependent and correlates with the extent of hepatic injury.